KONTRIBUSI KURS, SUKU BUNGA PERKREDITAN, DAN LIKUIDITAS, PADA PEMBIAYAAN PRODUKTIF BANK SYARIAH - Yovvi Sukandar; Muslim Marpaung (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2016)
This research was aimed to find out the contribution of exchange rate, interest rates of conventional banking, and the resilience of islamic banking liquidity towards produktive financing performance of islamic banking in  Indonesia during the last 10 years. By quantitative approach of VAR (Vector Auto Regressive) analysis at alpha 5%, concluded that the exchange rate,  interest rates of conventional commercial banks, and the condition of islamic banks liquidity contribute to productive financing  performance of islamic banks. The most contribution to productive financing growth sourced by the power of islamic banks liquidity (16,68%), followed by interest rates of conventional commercial banks  (4,97%), and rupiah exchange rate  (1,39%). Productive financing performance showed positive respon but tend to be difficult to stable against the movement rupiah exchange rate, the interest rates of conventional commercial banks, while in contrast to the power of liquidity variable that responded positively and tend to be stable and balanced.